Causal association between serum total bilirubin and cholelithiasis: a bidirectional two-sample Mendelian randomization study - Sun, Yang; Yang, Shaojie; Dai, Wanlin; Zheng, Zhuyuan; Zhang, Xiaolin; Zheng, Yuting; Wang, Jingnan; Bi, Shiyuan; Duan, Yunlong; Wu, Shuodong; Kong, Jing (Frontiers in Endocrinology, 2023)
Abstract Background: Observational studies about the association between serum total bilirubin and cholelithiasis are inconsistent. So, it is essential to reevaluate the association between serum total bilirubin and cholelithiasis and to verify if such association is causal or not. Methods: We selected single nucleotide polymorphisms (SNPs) strongly associated with exposure as instrumental variable and conducted a bidirectional two-sample mendelian randomization (MR) study to explore the causal association between serum total bilirubin and cholelithiasis. We implemented the inverse-variance weighted (IVW) approach as a primary analysis to combine the Wald ratio estimates. Four additional analyses, including MR-Egger regression, weighted median, weighted mode, and MR-PRESSO, were utilized to investigate the causal association and the influence of potential pleiotropy. Results: 116 SNPs were selected as valid instrumental variables to estimate the causal association of serum total bilirubin on cholelithiasis and causal association between genetically determined serum total bilirubin and cholelithiasis was demonstrated (beta = 0.10, 95% CI: 0.07 to 0.14, p < 0.001). Likewise, the other methods including the weighted median(beta = 0.12, 95% CI: 0.08 to 0.15, p < 0.001), MR Egger(beta = 0.11, 95% CI: 0.08 to 0.15, p < 0.001) , weighted mode(beta = 0.11, 95% CI: 0.08 to 0.15, p < 0.001) and MR-PRESSO approaches further confirmed this result(p = 0.054) indicates similar results. Also, 7 SNPs were selected as instrumental variable to estimate causal association of cholelithiasis on serum total bilirubin and the result supported causal effect of cholelithiasis to serum total bilirubin (beta = 0.12, 95% CI: 0.09 to 0.15, p < 0.001). At the same time, the other methods including the weighted median (beta = 0.10, 95% CI: 0.06 to 0.13, p < 0.001), MR Egger (beta = 0.12, 95% CI: 0.07 to 0.18, p = 0.007), weighted mode(beta = 0.09, 95% CI: 0.03 to 0.14, p = 0.019) and MRPRESSO methods further confirmed this result (p < 0.001). Conclusion: Our MR study revealed that the serum total bilirubin was causaly associated with the risk of cholelithiasis, and the genetic predisposition to cholelithiasis was causally associated with the increased serum total bilirubin levels.